2018
DOI: 10.1016/j.ijom.2018.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Significant association of increased PD-L1 and PD-1 expression with nodal metastasis and a poor prognosis in oral squamous cell carcinoma

Abstract: Programmed cell death ligand 1 (PD-L1) and its receptor PD-1 are immune checkpoint molecules that attenuate the immune response. Blockade of PD-L1 enhances the immune response in a variety of tumours and thus serves as an effective anti-cancer treatment. However, the biological and prognostic roles of PD-L1/PD-1 signalling in oral squamous cell carcinoma (OSCC) remain to be elucidated. The purpose of this study was to examine the correlation of PD-L1/PD-1 signalling with the prognosis of OSCC patients to asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
70
4

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(81 citation statements)
references
References 30 publications
7
70
4
Order By: Relevance
“…These other antibodies appear to have minimal differences among them. Differences in PD-L1 positivity detection between clones E1L3N and 22C3 in our study respectively ranged between 9.7% and 14.4%, whereas PD-L1 immunopositivity in HNSCC has been reported to range widely between 18% (58) and 100% (37)(38)(39)(40)(41)59). These varying results could be attributed to the heterogeneity in tumor samples, different stained protocols, and the variability in threshold or cut-off values for defining positive expression in different studies more than a true difference among the biological basis of OSCC in different studies.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…These other antibodies appear to have minimal differences among them. Differences in PD-L1 positivity detection between clones E1L3N and 22C3 in our study respectively ranged between 9.7% and 14.4%, whereas PD-L1 immunopositivity in HNSCC has been reported to range widely between 18% (58) and 100% (37)(38)(39)(40)(41)59). These varying results could be attributed to the heterogeneity in tumor samples, different stained protocols, and the variability in threshold or cut-off values for defining positive expression in different studies more than a true difference among the biological basis of OSCC in different studies.…”
Section: Discussioncontrasting
confidence: 51%
“…Various studies have investigated potential correlations of tumor PD-L1 expression with the clinicopathologic features and survival; however, evidences for a prognostic role of PD-L1 across a wide range of tumor types are inconsistent and ambiguous. Thus, although Maruse and colleagues (37) reported a significant relationship between PD-L1 expression and cervical lymph node metastasis and distant metastasis, Kim and colleagues (38) and Cho and colleagues (39) did not find any prognostic implications. Moreover, Oliveira-Costa and colleagues (28) observed worse prognosis in HNSCC with decreased PD-L1 expression, whereas Lin and colleagues (26) and Straub and colleagues (40) concur about a worse prognosis in OSCC with marked PD-L1 expression.…”
Section: Discussionmentioning
confidence: 91%
“…Recent research efforts have suggested that although squamous cell carcinoma of the oral tongue may be genomically similar in young and older patients, the principle biological difference between younger patients without a history of tobacco or alcohol exposure appears to be lie in the TME with younger patients demonstrating higher levels of PDL‐1 expression on the surfaces of tumor cells and higher intratumoral cytotoxic CD8 lymphocyte infiltration. The full biological role of PD‐1/PD‐L1 signaling in the formation and progression of oral squamous cell carcinomas remains to be elucidated, but there is evidence that increased expression is correlated with higher rates of cervical lymph node metastasis and worse prognosis …”
Section: Discussionmentioning
confidence: 99%
“…Antagonists of PD-1 and PD-L1 have demonstrated clinical utility in several types of advanced malignancies [32]. In OSCC, PD-L1/PD-1 expression is a useful predictor for nodal metastasis and poor prognosis in OSCC cases [33]. …”
Section: Hallmarks Of Cancer-related Conventional Principal Prognomentioning
confidence: 99%